Possibilities of using platelet-rich plasma in medicine, cosmetology and veterinary medicine. Review article. - Uniejewska, Sylwia Wanda (Journal of Education, Health and Sport, 2018)
Platelet rich plasma (PRP) is an autologous preparation obtained from blood. It has an increased number of platelets, and thus a high concentration of growth factors involved in the tissue renewal of the body. Platelet rich plasma is currently widely used in medicine, cosmetology and veterinary medicine. The method of obtaining PRP and an overview of its most common applications is presented below.